The role of frailty score in early surgical treatment of elderly cholecystitis patients - Turhan, Nihan; Duran, Cengiz; Ertorul, Didem; Bulut Batur, Ülkü (The European Research Journal, 2023)
Objectives: The average life expectancy is increasing all over the world, and as a result, the number of elderly patients is increasing. Acute cholecystitis is one of the most common diseases requiring emergency surgical treatment in the elderly. In the literature, it has been reported that in the treatment of elderly patients with acute cholecystitis, physicians do not fully comply with the current literature recommendations due to some concerns and do not apply surgical treatment in the early period. The concept of frailty, which has come to the fore in geriatric assessment today, provides objective information about the general health status of the patient. In our study, the role of frailty assessment in the decision made regarding the early surgery in elderly patients with acute cholecystitis treated in our hospital was investigated. Methods: In our study, the clinical features, comorbidities, American Society of Anesthesiologists (ASA) scores, Canadian Study of Health and Aging (CSHA) frailty scale, treatment modalities and prognosis of patients over the age of 65 who were treated with the diagnosis of acute cholecystitis between January 2018 and January 2021 were evaluated retrospectively. Results: Of the 182 patients included in the study, 24 (13.2%) were found to be frail. It was observed that the mean age and multi-morbidity were higher in the frail group (p < 0.001). It was observed that the mean C-reactive protein and leukocyte values, which are inflammatory mediators, increased in both groups, both fragile and non-fragile, and complicated cholecystitis accompanied by cholangitis or pancreatitis was observed in a total of 64 (35.16%) patients. There were 57 (31.3%) patients using anticoagulant or antiaggregant agents. The patients were most frequently treated with medical treatment (n = 108; 59.3%), the other treatment methods were early surgery ( (n = 46; 25.3%), endoscopic retrograde cholangiopancreatography (n = 22; 12.1%) and percutaneous cholecystostomy (n = 11; 6.0%). Surgical treatment was more common in ASA I and II patients, and percutaneous cholecystostomy was more common in frail patients (p < 0.001). There were 20 (14.70%) patients who were re-admitted to the hospital and 6 (3.29%) patients ended up with mortality. No statistical relationship could be demonstrated between these conditions and frailty (p > 0.05). Conclusions: In the treatment of the elderly cholecystitis patients, early surgical treatment is the most favorable treatment method in order to reduce re-admission and prevent possible complications. However, we think that a detailed geriatric evaluation should be made in a multidisciplinary manner for the decision making regarding the of surgical treatment of elderly patients, and frailty evaluation should also be made in this context.